The Cryosphere and Bofedales Sustain Water Security in the Arid Andes of Southern Peru - Valcarcel, Marcos (2025)
The Coropuna volcanic complex (15º31’S, 72º39’W; 6377 m a.s.l.) is located on the western slope of the Peruvian Andes. It comprises several stratovolcanoes whose summits exceed 6,000 m in elevation and are covered by the most extensive glacial system in the tropical zone (40 km² as of 2024). These glaciers, which may have persisted throughout the Pleistocene, likely descended multiple times to the surrounding Altiplano, potentially following the ~100 ka cyclicity inferred from proglacial sediments of Lake Junín over the past ~700 ka. Cosmogenic exposure dating indicates that around ~14 ka, Coropuna's glaciers descended to altitudes below the Altiplano (<4,000 m), coinciding with the transgressions of paleolakes in the Bolivian Altiplano and a southward displacement of the Intertropical Convergence Zone driven by Northern Hemisphere cooling. According to reconstructions from the Bolivian Altiplano⁴, the depression of the paleo-ELA at Coropuna (~1,000 m) suggests that the climate was colder (−6.4 °C) and more humid than today, with precipitation rates 1.2–2.8 times higher than present. Throughout the Holocene, permafrost has developed where glaciers retreated to summit areas under favorable conditions of high surface albedo and south-facing orientation. Both glacier retreat and the cycles of permafrost development and degradation have been linked to La Niña/El Niño phases of the ENSO phenomenon. Currently, Coropuna represents a tropical high mountain environment characterized by extreme conditions: high elevation, intense solar radiation, and a semi-arid climate, with precipitation concentrated during the austral summer and reaching ~600 mm annually in the highest areas. Under these conditions, the cryosphere (glaciers, rock glaciers, and permafrost) is highly sensitive to the impacts of contemporary climate change, and its melting sustains tropical high-altitude peatlands. Unlike other types of peatlands, the bofedales—as these wetland ecosystems are known in the Central Andes—develop in cold, semi-arid environments, generally between 3,800 and 5,000 meters, and are dominated by plant species such as Distichia muscoides Nees & Meyen, Oxychloe andina Phil., Plantago sp., and Carex sp. These peatlands play a crucial ecological role: they function as natural sponges, storing water during the wet season and releasing it gradually during the dry season. In doing so, the high Andean bofedales regulate water resources that support livestock, wildlife at higher elevations, and tens of thousands of people and their economic activities downstream within the drainage basins. Furthermore, bofedales are key ecosystems for climate change mitigation due to their high carbon sequestration capacity. Periglacial landforms identified during fieldwork (e.g., rock glaciers, cryoplanation terraces, polygonal soils, and tors) provide evidence of active permafrost dynamics at elevations above 4,500 m. Down-valley, bofedales have been documented between 3,800 and 4,500 m, occurring in various geomorphological contexts, with peat thicknesses reaching 4 meters in isolated Altiplano sectors and up to 10 meters in the floors of deeply incised glacial valleys. The objective of this study is to highlight the interactions among glaciers, permafrost, and peatlands, and their collective role in sustaining water reserves in the context of an arid mountain landscape inhabited by ancestral communities (Fig. 1).